Ugrabljena ljubezen = Oteta ljubav = Abducted Love Priročnik za pouk državljanske vzgoje = Priručnik za nastavu građanskog vaspitanja = Workbook for the teaching about civic education - Petrović, Tanja (Moj zvezek = Moja sveska = My Workbook, 2011)
The contributions thematise love to a homeland in groups and individuals who fail to conform to the dominant understanding of patriotism~this often renders them inapt patriots and they are, hence, symbolically deprived of loving their homeland. The authors thematise love for homeland(s) in im/migrants, members of ethnic and sexual minorities, mixed marriage children, anarchists and social critics and activists. The authors and the people depicted stand for understanding and practicing the so-called critical patriotism, a practice best subsumed in the phrase: "use your mind".